PENGEMBANGAN BUDAYA ORGANISASI DENGAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT DI PT XYZ - Yusri, Ryyld Ipbtas (Research Center and Case Clearing House PPM School of Management, 2011)
In the year 1998-2010, PT XYZ have faced a tough business challenges. Therefore PT XYZ have establish a new strategic direction to ensure sustainable growth in long term period. Either one of that strategic is to develop high performance culture as enabler to achieve itâ€™s vision in 2020. However currently, PT XYZ have not had a comprehensive design how to develop organization culture. So the porpuse of this studi to describe the dominant culture type in both current and preferred situation as weel as by good right culture type which is aligned with the executives talent in PT XYZ. This study based on the Organizational Culture Assessment Instrument (OCAI) built upon a theoretical model called the â€œCompeting Values Frameworkâ€. This framework refers to whether an organization has predominant internal or external focus and whether it strives for flexibility or stability. Moreover, the purpose of the OCAI is to assess six key dimensions of organization culture. The results of this study showed that current organization culture is Hierarchy which is driven by efficiency, consistency and uniformity values. However, the preferred or the should be organization culture is Market which is driven by goal achievement and competitiveness values. Fortunately, the PT XYZâ€™s executive talent have align with preferred culture so that it can ease to develop new organization culture. Several initiatives can be purposed to manage the change of the corporate culture. The initiatives consist of leadership role alignment, consistent communication, improve employees capability and optimize systems and procedures.